If $\int \frac{2 e^{x}+3 e^{-x}}{4 e^{x}+7 e^{-x}} d x=\frac{1}{14}\left(u x+v \log _{e}\left(4 e^{x}+7 e^{-x}\right)\right)+C$ where $C$ is a constant of integration, then $u+v$ is equal to
$\int \frac{2 e^{x}}{4 e^{x}+7 e^{-x}} d x+3 \int \frac{e^{-x}}{4 e^{x}+7 e^{-x}} d x$
$=\int \frac{2 \mathrm{e}^{2 \mathrm{x}}}{4 \mathrm{e}^{2 \mathrm{x}}+7} \mathrm{~d} \mathrm{x}+3 \int \frac{\mathrm{e}^{-2 \mathrm{x}}}{4+7 \mathrm{e}^{-2 \mathrm{x}}} \mathrm{dx}$
Let $\quad 4 \mathrm{e}^{2 \mathrm{x}}+7=\mathrm{T} \quad$ Let $\quad 4+7 \mathrm{e}^{-2 \mathrm{x}}=\mathrm{t}$
$8 \mathrm{e}^{2 \mathrm{x}} \mathrm{dx}=\mathrm{dT}$ $-14 \mathrm{e}^{-2 \mathrm{x}} \mathrm{dx}=\mathrm{dt}$
$2 \mathrm{e}^{2 \mathrm{x}} \mathrm{dx}=\frac{\mathrm{dT}}{4} \quad \mathrm{e}^{-2 \mathrm{x}} \mathrm{dx}=-\frac{\mathrm{dt}}{14}$
$\int \frac{\mathrm{dT}}{4 \mathrm{~T}}-\frac{3}{14} \int \frac{\mathrm{dt}}{\mathrm{t}}$
$=\frac{1}{4} \log \mathrm{T}-\frac{3}{14} \log \mathrm{t}+\mathrm{C}$
$=\frac{1}{4} \log \left(4 \mathrm{e}^{2 \mathrm{x}}+7\right)-\frac{3}{14} \log \left(4+7 \mathrm{e}^{-2 \mathrm{x}}\right)+\mathrm{C}$
$=\frac{1}{14}\left[\frac{1}{2} \log \left(4 \mathrm{e}^{\mathrm{x}}+7 \mathrm{e}^{-\mathrm{x}}\right)+\frac{13}{2} \mathrm{x}\right]+\mathrm{C}$
$\mathrm{u}=\frac{13}{2}, \mathrm{v}=\frac{1}{2} \Rightarrow \mathrm{u}+\mathrm{v}=7$
Aliter :
$2 \mathrm{e}^{\mathrm{x}}+3 \mathrm{e}^{-\mathrm{x}}=\mathrm{A}\left(4 \mathrm{e}^{\mathrm{x}}+7 \mathrm{e}^{-\mathrm{x}}\right)+\mathrm{B}\left(4 \mathrm{e}^{\mathrm{x}}-7 \mathrm{e}^{-\mathrm{x}}\right)+\lambda$
$2=4 \mathrm{~A}+4 \mathrm{~B} \quad ; \quad 3=7 \mathrm{~A}-7 \mathrm{~B} \quad ; \quad \lambda=0$
$\mathrm{A}+\mathrm{B}=\frac{1}{2}$
$\mathrm{A}-\mathrm{B}=\frac{3}{7}$
$\mathrm{A}=\frac{1}{2}\left(\frac{1}{2}+\frac{3}{7}\right)=\frac{7+6}{28}=\frac{13}{28}$
$\mathrm{~B}=\mathrm{A}-\frac{3}{7}=\frac{13}{28}-\frac{3}{7}=\frac{13-12}{28}=\frac{1}{28}$
$\int \frac{13}{28} \mathrm{dx}+\frac{1}{28} \int \frac{4 \mathrm{e}^{\mathrm{x}}-7 \mathrm{e}^{-\mathrm{x}}}{4 \mathrm{e}^{\mathrm{x}}+7 \mathrm{e}^{-\mathrm{x}}} \mathrm{dx}$
$\frac{13}{28} x+\frac{1}{28} \ell n\left|4 e^{x}+7 e^{-x}\right|+C$
$\mathrm{u}=\frac{13}{2} ; \mathrm{v}=\frac{1}{2}$
$\Rightarrow \mathrm{u}+\mathrm{v}=7$